Salvage high‐intensity focused ultrasound (HIFU) for locally recurrent prostate cancer after failed radiation therapy: Multi‐institutional analysis of 418 patients. (10th March 2017) - Crouzet, Sebastien; Blana, Andreas; Murat, Francois J.; Pasticier, Gilles; Brown, Stephen C. W.; Conti, Giario N.; Ganzer, Roman; Chapet, Olivier; Gelet, Albert; Chaussy, Christian G.; Robertson, Cary N.; Thuroff, Stefan; et al.
Abstract : Objective: To report the oncological outcome of salvage high‐intensity focused ultrasound (S‐HIFU) for locally recurrent prostate cancer after external beam radiotherapy (EBRT) from a multicentre database. Patients and Methods: This retrospective study comprises patients from nine centres with local recurrent disease after EBRT treated with S‐HIFU from 1995 to 2009. The biochemical failure‐free survival (bFFS) rate was based on the 'Phoenix' definition (PSA nadir + 2 ng/mL). Secondary endpoints included progression to metastasis and cancer‐specific death. Kaplan–Meier analysis was performed examining overall (OS), cancer‐specific (CSS) and metastasis‐free survival (MFS). Adverse events and quality of life status are reported. Results: In all, 418 patients with a mean (SD) follow‐up of 3.5 (2.5) years were included. The mean (SD) age was 68.6 (5.8) years and the PSA level before S‐HIFU was 6.8 (7.8) ng/mL. The median PSA nadir after S‐HIFU was 0.19 ng/mL. The OS, CSS and MFS rates at 7 years were 72%, 82% and 81%, respectively. At 5 years the bFFS rate was 58%, 51% and 36% for pre‐EBRT low‐, intermediate‐ and high‐risk patients, respectively. The 5‐year bFFS rate was 67%, 42% and 22% for pre‐S‐HIFU PSA level ≤4, 4–10 and ≥10 ng/mL, respectively. Complication rates decreased after the introduction of specific post‐RT parameters: incontinence (grade II or III) from 32% to 19% ( P = 0.002); bladder outlet obstruction or stenosis from 30% to 15% ( P = 0.003); recto‐urethral fistula decreased from 9% to 0.6% ( P < 0.001). Study limitations include being a retrospective analysis from a registry with no control group. Conclusion: S‐HIFU for locally recurrent prostate cancer after failed EBRT is associated with 7‐year CSS and MFS rates of >80% at a price of significant morbidity. S‐HIFU should be initiated early following EBRT failure